Managing Tacit Knowledge Sharing: From Charismatic Leadership to Psychological Safety Climate - Dhaniel Hutagalung; Admiral Admiral; Yulis Nuryanti; Masduki Asbari; Dewiana Novitasari (Inovbiz: Jurnal Inovasi Bisnis, 2021)
This study aims to examine the effect of charismatic leadership on the psychological safety climate and tacit knowledge sharing. This study also investigates the central role of psychological safety climate as a mediating variable between charismatic leadership and tacit knowledge sharing. This study adopted a simple random sampling method with 61 samples of employees from five of MSME companies in Banten. With the help of SmartPLS 3.0 software, the results of this study indicate that charismatic leadership has a significant direct influence on the psychological safety climate and tacit knowledge sharing. Likewise, the psychological safety climate has a significant direct effect on tacit knowledge sharing. This study also found evidence that charismatic leadership has a significant indirect effect on tacit knowledge sharing through mediating the psychological safety climate. Thus, the psychological safety climate acts as a partial mediator in this research model.